2008
DOI: 10.1007/s00063-008-1041-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation der Fortbildung: Einfluss des Sponsorings im Urteil der Teilnehmer

Abstract: Sponsored and unsponsored CME events are rated as equally satisfactory by the great majority of participants. Only in about 8% of the evaluation forms a commercial bias was noted, which had a negative impact on the educational value of the CME event. Thus, it seems most likely that the regulatory framework for accreditation is able to prevent large-scale commercial influence on CME events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Indeed, in a recent US survey, 88% of participants believed that industry-derived financial supported CME activities were subject to bias 13 . Other research from Germany and the US has indicated that industry-funded CME programmes are statistically equivalent to non-commercially supported CME activities in the degree of detectable bias present 14,15 , underscoring the point that there are numerous potential sources of bias, that include intellectual and professional as well as financial biases. This point was recently acknowledged by the European Society of Cardiology in their CME policy document, which concluded that financial sources of bias must be acknowledged by full disclosure 16 .…”
Section: Independence and Transparencymentioning
confidence: 98%
“…Indeed, in a recent US survey, 88% of participants believed that industry-derived financial supported CME activities were subject to bias 13 . Other research from Germany and the US has indicated that industry-funded CME programmes are statistically equivalent to non-commercially supported CME activities in the degree of detectable bias present 14,15 , underscoring the point that there are numerous potential sources of bias, that include intellectual and professional as well as financial biases. This point was recently acknowledged by the European Society of Cardiology in their CME policy document, which concluded that financial sources of bias must be acknowledged by full disclosure 16 .…”
Section: Independence and Transparencymentioning
confidence: 98%